Floristic relationship between scrubland and grassland patches in the Mediterranean landscape of the Iberian Peninsula - Ramirez-Sanz, L; Casado, M A; Miguel, J M De (Plant Ecology, 2000)
In the rural Mediterranean landscape, mosaics of patches of sclerophyllous scrubland and semi-natural grasslands are frequent. The plant communities of these patches, which are physiognomically easy to recognise, are very heterogeneous. The objective of this paper is to determine whether the patches of scrub-grassland represent an integrated response unit of the vegetation with regard to the physical environment (climatic, geographical and edaphic factors) and human use, or whether, on the contrary, this is an independent response. In order to do this a total of 50 sampling sites where scrubland and grassland patches were in contact were studied along a 370 km E-W mesoclimatic gradient from central Spain to Portugal (Iberian Peninsula). Two distinct zones, the east and the west halves of the study area, were identiﬁed according to the plant communities. Within each of these zones, each type of patch responded to the previously mentioned factors, differentially and independently. This determined a general lack of inter-community association or ﬂoristic correlation between scrub and grassland plant communities in contact. The spatial association is a random process probably related to the particular human management realised on every scrubland and grassland patch. The scrub–grassland pattern, which is characteristic of the Mediterranean landscape, does not represent an integrated response unit of the vegetation to a given environment, but rather the sum of the independent responses to the environment of the two patches in contact.
Keywords: environmental gradient; inter-community association; mediterranean scrubland; rural landscape; spatial association; therophyte grasslands

Production and spatial structure of Mediterranean pastures in different stages of ecological succession - Casado, M A; Miguel, J M; Sterling, A; Peco, B (Plant Ecology, 1986)
The aim of this paper is to describe the changes of Mediterranean pasture phytomass and their dependence on succession, slope geomorphology and herbivore consumption. Four neighbouring slopes of similar aspect and steepness, located in a pasture area of Central Spain, were chosen for sampling. The slopes had not been cultivated for 1, 3, 8 and 40 years respectively. On each slope both the upper, erosion zone and the lower, accumulation zone were sampled during the months of plant growth (April to July), phytomass being record- ed in plots where herbivore consumption was avoided with protection cages and in unprotected plots. Results from the protected plots show that the upper and lower parts of slopes undergo a different develop- ment during succession. The highest values of phytomass reached, tended to decrease during succession in the upper zones, the same being true for production. However in the lower zones both parameters tended to increase in time. The ratio P/B, widely known in ecology to decrease with time, did not seem to behave as a usual index of succession in the studied ecosystem. In the upper zone this ratio tended to decrease but in the lower zone it increased with succession after the first years. Phytomass consumption by herbivores was progressively concentrated during succession in the slope sec- tors of greater production, mainly in the lower zone, which increased its productivity as the slope-talweg sys- tem became functional. The evolution of the ecological structure of a slope should be interpreted not only as a result of the tolerance of species to phsysico-chemical factors. It may also reveal the existence of an im- portant interaction between the pasture and the grazing behaviour of exploiting animals. Multivariate analy- sis of phytomass records revealed a trend of temporal variation which should be identified with the progress
Keywords: herbivore consumption; mediterranean pasture; primary production; slope geomorphology; spatial structure of phytomass; succession

Successional changes in the morphology and ecological responses of a grazed pasture ecosystem in Central Spain - Sal, A Gomez; Miguel, J M; Casado, M A; Pineda, F D (Plant Ecology, 1986)
Morphological characteristics related to spatial occupation, reproduction and adaptations to grazing were used to characterize the most frequent species in a therophytic pastureland of Central Spain. Periodic ploughing is a traditional practice in these pastures and allows observation of successional change. In the present study, four neighbouring slopes of differing time since last ploughing were chosen. Species biomass was measured at different times during the annual growing season for two different slope positions. Grazing pressure is an important environmental factor affecting ecosystem organization, the most palata- ble plants tending to show increasing biomass with succession. In the most mature stages, there is a predomi- nance of species characterized by horizontal occupation of space and sprouting after mowing or grazing. During succession segregation of the different morphological characteristics occurs in slope sectors related to geomorphological dynamics. Similarly, phenological development tends to be later in pastures in the lowest slope zones, due probably to their greater summer soil moisture content.
Keywords: ecosystem exploitation; Grazing; herbivore; mediterranean pasture; Phenology; phytomass; Plant morphology; succession